CLIMATE-INFORMED ECOLOGICAL MONITORING OF ZELI LAKE: REMOTE SENSING AND FIELD APPROACHES - Ulviyya Mammadova; Fuad Guliyev; Elchin Aliyev (Asian Journal of Aquatic Sciences, 2025)
The ecological and tourism potential of Zeli Lake has been assessed using remote sensing techniques based on aerospace data. Using OpenStreetMap and Google Earth, the eco-geographical features of the lake were identified from these materials. The lake covers approximately 2,551 m² (0.26 ha) and has a total perimeter of 202.4 m. Its absolute altitude is around 909 m above sea level, while the relative altitude (eye altitude) reaches 1.37 km. From a satellite view, the lake has an oval, leaf-like shape. According to Google Earth measurements, its map length is 76.60 m and ground length is 76.96 m with a heading of 193.43°. The width is 63.37 m on the map and 63.39 m on the ground, with a heading of 90.59°. The exact geographic location of the Lake is 40°24′24.6″ N, latitude, and 46°23′10.8″ E longitude. So far, the ecotourism resources of the research object have not been comprehensively studied. In this respect, the lake's climatic conditions were analyzed using Landsat satellite imagery, other remote sensing data, and field visits. Seasonal monitoring was conducted to assess climate, forest cover, and visitor activity. The woodland surrounding the lake covers about 0.88 ha within a perimeter of 678 m. The area remains largely undeveloped, with only a small café located on the shore; no cottages, hotels, or hostels exist nearby. During autumn migration, several bird species are observed around the lake. Many of these belong to the species listed in the “Green Book” and “Red Book” of the Republic of Azerbaijan. In conclusion, the lake itself is a valuable natural site with promising ecotourism opportunities. However, its ecosystem has not yet been fully investigated, and further interdisciplinary research is required to evaluate and sustainably develop its resources.